2020
DOI: 10.1371/journal.pone.0227325
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of risk and influences of choice in pregnant women with obesity. An evidence synthesis of qualitative research

Abstract: Background Between 7-35% of the maternity population are obese in high income countries and 1-40% in lower or middle-income countries. Women with obesity are traditionally limited by the choices available to them during pregnancy and birth because of the higher risk of complications. This evidence synthesis set out to summarise how women with obesity's perceptions of pregnancy and birth risk influence the care choices that they make. Methods A search of medical and health databases for qualitative studies writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…An important consideration proposed by Relph et al [40] who described that discussions around pregnancy risk between women with obesity and their healthcare provider appeared to be avoided unless risk arose, suggesting there may be reluctance from both HCPs and women to initiate discussion about risk. It may be that HCPs are concerned of introducing unwarranted anxiety over potential risks that may not occur [40], although Garrud, Wood, and Stainsby [41] reported that providing detailed risk information was associated with greater knowledge with no increase in anxiety. Limited information provided may give women a false sense of security in their perception of pregnancy risk.…”
Section: Plos Onementioning
confidence: 99%
“…An important consideration proposed by Relph et al [40] who described that discussions around pregnancy risk between women with obesity and their healthcare provider appeared to be avoided unless risk arose, suggesting there may be reluctance from both HCPs and women to initiate discussion about risk. It may be that HCPs are concerned of introducing unwarranted anxiety over potential risks that may not occur [40], although Garrud, Wood, and Stainsby [41] reported that providing detailed risk information was associated with greater knowledge with no increase in anxiety. Limited information provided may give women a false sense of security in their perception of pregnancy risk.…”
Section: Plos Onementioning
confidence: 99%
“…As regards capabilities, it was demonstrated that there is need to find consistent ways to broach the topic of overweight. Both health care professionals and pregnant women seem to avoid discussion regarding obesity and weight-management [27]. Health technology, such as smart wearables could be utilized as part of antenatal care and a means of introducing the topic of weight and weight management.…”
Section: Discussionmentioning
confidence: 99%
“…Women with obesity are already at increased risk of many obstetric complications including preeclampsia, gestational diabetes, venous thromboembolism, and need to deliver by CD, as well as neonatal morbidity and mortality 15 . A recent evidence synthesis regarding perception of pregnancy risks in women with obesity has shown that women with obesity felt fearful of consultations because of the perceived stigma around being obese, which led to perceived over‐inflation of the risks 21 . It is therefore important to clarify to clinicians that obesity is not associated with increased risk of PAS to avoid further unnecessary anxiety.…”
Section: Discussionmentioning
confidence: 99%